A functional assay to identify amyloidogenic light chains. (3rd April 2018) - Martin, Emily B.; Williams, Angela D.; Heidel, R. Eric; Foster, James S.; Lands, Ronald H.; Kennel, Stephen J.; Wall, Jonathan S.
Abstract: Introduction: Multiple myeloma (MM) and light chain monoclonal gammopathy of undetermined significance (LCMGUS) are plasma cell disorders associated with the secretion of monoclonal free light-chain (LC) proteins. Due to the high concentrations of LC in circulation, both of these populations are at risk for developing LC-associated amyloidosis (AL) – a protein misfolding disease characterized by the deposition of LC protein fibrils in organs and tissues, leading to dysfunction and significant morbidity. At present, accurate identification of subjects at risk for developing amyloidosis is not possible, but with the advent of novel, amyloid-targeted therapies, identification of pre-symptomatic individuals is of clinical import. Methods: To address this, a competition assay has been developed to discern LC proteins with enhanced amyloidogenic potential. Numerous factors that may influence the efficacy of the assay have been evaluated to yield optimal conditions. Results: Using a panel of nine patient-derived LC, we have demonstrated that amyloid-associated LC inhibited the recruitment of a biotinyl-λ6 variable domain by homologous amyloid-like fibrils significantly more than MM LC ( p  < .01). Conclusion: The assay accurately discriminated AL from MM patient populations, suggesting that it may aid in the identification of patients with monoclonal gammopathies who have an increased risk of developing amyloidosis.